A Review on Fiber Properties, Manufacturing, and Crashworthiness of Natural Fiber-Reinforced Composite Structures - Mahaboob Subhani Shaik; Hariharan Sankara Subramanian; Ravi Kumar B.; Indran Suyambulingam; P Senthamaraikannan; R. Kumar (Journal of Natural Fibers)
Research into natural fibre-reinforced polymer composites (NFRCs) has intensified because society demands sustainable biodegradable substitutes for synthetic composites. This paper investigates plant-based natural fibres from cultivation up until extraction, followed by chemical treatments before manufacturing stages, while analyzing their resulting mechanical and thermal characteristics. This paper specifically investigates NFRCs crashworthiness through examinations of failure modes and energy absorption mechanisms together with investigations of structural geometry and fibre volume fraction and orientation effects. The study explains different manufacturing processes, including hand lay-up and compression molding, as well as vacuum bagging and bladder molding, because their influence on mechanical performance needs assessment. Current research approaches the following issues: weak bond strength between fibre and matrix, and moisture sensitivity, while outlining future perspectives that focus on advanced chemical transformation and bio-resin combination approaches. The comprehensive guide provides instructions for selecting materials along with designing structures for energy-absorbing lightweight solutions and environmentally friendly applications in the transportation and aerospace industries.